The Effect of Advertainment toward The Affective Motivations of Online Customer Brand Engagement - Liu, Yen-Chun (2014)
In the marketing environment with fierce competition, the development of the social networking sites (SNS) leads to the customers’ willing to actively engage with the brands they like. The improving on customer brand engagement might cause the positive long-term relationship between customers and the brands. For attracting the awareness from customers, many organisations provide a myriad of advertainment campaign, which including images, music, stories, and interactive activities. Therefore, in order to discuss the topics of CBE and advertainment, the purpose of this research is discovering whether or not the affective motivations of online CBE will be affected by advertainment content, and explore what factors from advertainment contents could cause the affective motivations of online CBE. Moreover, this study decided to conduct qualitative research method, via in-depth semi-structured interview process to find out the key issues. The research discoveries that the entertainment and social interaction needs present positively influence on the affective motivations of online CBE. The entertainment related factors show more influence than the factors of social interaction. From the entertainment perspective, the advertainment content includes the characteristics of incongruity and superiority is more likely to meet the entertainment needs of customers. From the social interaction point of view, although the convenient social connection leads to positive CBE, the social identity and privacy issue are serious factors need to be concerned whilst the companies want to satisfy the social interaction needs. Keywords: customer brand engagement, advertainment, social networking sites